KAJIAN FAKTOR-FAKTOR DALAM PROSES PEMBANGUNAN DESA DI ERA OTONOMI DAERAH DI KECAMATAN SINONSAYANG - Mareine Warouw; Ricky Leonardus Rengkung; Paulus Adrian Pangemanan (Sam Ratulangi University, 2015)
The purposes of this research are: 1) describes the process of rural development in Sub Sinonsayang; 2) examine the factors in the development process of regional autonomy era village in the district of South Minahasa regency Sinonsayang. The method used in a descriptive study using a quantitative approach, among others, using a Likert scale, ie research which is then processed and analyzed to be concluded, using primary and secondary data. Primary data is data obtained directly in the field through direct interviews with respondents. Secondary data were obtained from the District Office and the Central Bureau of Statistics Sinonsayang South Minahasa District. The results showed that: first, the process of rural development in Sub Sinonsayang starting from the planning, implementation and maintenance of development. while the second: 1) factor of natural resources which consists of land owned by the community, the results and the types of commodity crops, and the number of livestock and meat production of commodity fish catches with the overall average amount is 2.59 and included in the category